2014 Elektro 2014
DOI: 10.1109/elektro.2014.6848981
|View full text |Cite
|
Sign up to set email alerts
|

Electrical properties of LiPO<inf>3</inf> glasses

Abstract: This paper reports on the electrical properties of LiP03 glass over a wide range of frequencies (10 Hz -2 MHz) and temperatures (290 K -627 K). The temperature dependence of a.c. conductivity is studied at different frequencies. The d.c. conductivity is due to the hopping of lithium ions. A theoretical model and mathematical fit of conductivity measurements are used for characterization of the ionic hopping motion connected with the mobility of conducting Li+ ions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…[ 53] And this result also verifies that some DFOB ‐ can be excluded from inner solvation shell and preferentially oxidized. Besides, TMP also contributes to the stable high voltage performance of cells with LHCEs, its oxidation product, PO3 could facilitate Li + transportation in the CEI [ 33,54] (Figure ). Therefore, LHCEs can promote the formation of inorganic‐rich CEI layers.…”
Section: Resultsmentioning
confidence: 99%
“…[ 53] And this result also verifies that some DFOB ‐ can be excluded from inner solvation shell and preferentially oxidized. Besides, TMP also contributes to the stable high voltage performance of cells with LHCEs, its oxidation product, PO3 could facilitate Li + transportation in the CEI [ 33,54] (Figure ). Therefore, LHCEs can promote the formation of inorganic‐rich CEI layers.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies [ [4] , [5] , [6] , [7] ] have shown that Li 2 O–P 2 O 5 glass is an excellent fast-conducting glass for Li + ions. One of the strategies embraced for augmenting conductivity involves introducing a doping salt, such as a metal halide (LiX, where X = Cl–, Br–, I–), into these glass compositions [ [8] , [9] , [10] ].…”
Section: Introductionmentioning
confidence: 99%
“…[16] LiPO 3 is also finding new applications for the production of the next generation of LIBs with solid electrolytes. [17][18][19] This phosphate glass, like other types of glasses, namely oxides, doped oxides, sulphides, fluorides, and quenched glasses, have long been known as potential solid electrolytes for high energy density batteries. [20] Due to the lack of grain boundaries, plasticity, weak electronic contribution to the conductivity, and the possibility of manufacturing them in thin-film configuration, they can serve as the ideal replacement for traditional non-aqueous liquid electrolytes, adding the advantages of nonflammability and miniaturization.…”
Section: Introductionmentioning
confidence: 99%